The Ambivalent Identitarian : Macanese Metamorphoses in Times of Change - Gaspar, Marisa C. (2021)
This article examines two different topics related to the concept of ambivalence and its phenomenological experience applied to the Eurasian Macanese community case study. The first section, from an ethnographic point of view, addresses a set of intersubjective dynamics of identification and differentiation developed by a group of friends during an intimate reunion of commensality. During this particular event, the social actors highlight their ambivalent condition, deploying this as an improvised and positive strategy to adapt to changeable external circumstances. Te second section recasts the narrative of Macao’s hybrid history, which lies at the origin of the Macanese community and characterises its permanent redefinition, thus drawing political and cultural dimensions into the discussion alongside the identity-building project implemented in the recently-established Macao Special Administrative Region (Macao SAR). In this case, there is an implicit ambivalence to the Sino-Portuguese negotiation process over the application of the People’s Republic of China nationality law to Macao-born residents, in particular to ethnically mixed Macanese, within the context of the handover of sovereignty to China.